Pengembangan Kurikulum Pendidikan dan Globalisasi - Ersi Ersi; Ahmad Mulyadi; Dwi Noviani; Hilmin Hilmin (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
The era of globalization will influence social, cultural, political developments and including Islamic education, both now and in the future. The era of globalization is marked by advances in Science and Technology (IPTEK) so that Islamic Religious Education must prepare students with 21st century skills. Globalization in the field of education has an impact on Islamic educational traditions, where the Islamic Religious Education curriculum generally studies religious knowledge, especially the study of yellow books (classics) regarding fiqh, monotheism, Sufism and nahwu nervous. The Islamic education curriculum essentially prioritizes values, human potential as the Khalifah of Allah SWT, unity, religion, self-development, at least individual self-development or the values ​​of life in society. To prepare students to face the era of globalization, curriculum development is needed, namely developing curriculum components. The aim of this research is to determine the era of globalization of education, the influence of globalization on Islamic educational traditions and curriculum development to face the era of globalization. The research method used is library research. From this research, it is clear that globalization has had a big influence on Islamic educational traditions, so all curriculum components must be developed to face the era of globalization which is related to 21st century life skills and the Society 5.0 era.